Hubungan Motivasi Dan Kepuasan Kerja Dengan Produktivitas Kerja Guru SD Di Gugus 1 Kecamatan Tanete Riattang Kabupaten Bone - Masniah, Masniah; Arismunandar, Arismunandar; Irfan, Muhammad (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study is an ex post-facto research that aims to find out whether there is a relationship between motivation and job satisfaction and the work productivity of elementary school teachers in cluster 1. The independent variables in this study are teachers' motivation and job satisfaction, while the bound variable is the work productivity of elementary school teachers in cluster 1. in this study, all school teachers in cluster 1, while the sample was elementary school teachers in cluster 1 spread across 12 schools totaling 35 teachers. The data of the research results was obtained by distributing written questionnaires in the form of questionnaires. Data analysis techniques in quantitative research use statistics, namely descriptive statistics and inferential statistics. The results of the study showed that  the picture of teachers' work motivation was good, teachers' job satisfaction was good, and teachers' work productivity was in the medium category. There was a significant positive relationship between motivation and job satisfaction with the work productivity of elementary school teachers in cluster 1, Tanete Riattang District, Bone Regency.